Traumatic Spondyloptosis: Neurological, Surgical, and Outcome Perspectives in a Tertiary Care Center - Rahul Singh; Ravi Shankar Prasad; Ashvamedh Singh; Kulwant Singh; Anurag Sahu (Indian Journal of Neurosurgery)
Objective To evaluate traumatic spondyloptosis cases for neurological, surgical, and outcome perspectives. Materials and Methods This retrospective study includes 17 patients of spondyloptosis admitted in our department between August 2016 and January 2020. Each patient was evaluated in terms of demographic profile, clinical presentation, duration of injury, mode of injury, associated injuries, level and type of spondyloptosis, spinal cord status, nociceptive and neuropathic pain severity, severity of injury based on International Standards for Neurological Classification of Spinal Cord Injury (ISNCSI) assessment, surgical approaches, complications, and outcome. Unpaired t- test and Chi-square test were used for statistical analysis. Values with p < 0.05 were considered statistically significant. Results Fall from height (58.8%) was the most common mode of injury. Most common level of spondyloptosis was T12–L1 (41.1%). Sagittal–plane spondyloptosis (76.5%) were more common than coronal–plane spondyloptosis (23.5%). Most common associated injury was musculoskeletal (64.7%). Neurological status of the patient at presentation (p = 0.0007) was significantly associated with outcome after 3 months of surgery/conservative management. Residual listhesis was present in 53.3% of patients postoperatively. Postoperative nociceptive pain (p = 0.0171) and neuropathic pain (0.0329) were significantly associated with residual listhesis. Duration of injury (p = 0.0228) was also significantly associated with postoperative residual listhesis. Conclusion Complete reduction of spondyloptosis should be the goal of surgery. Overall prognosis of spinal cord injury (SCI) due to traumatic spondyloptosis is poor.